How to Reform Business Licenses - International Finance Corporation; World Bank (Washington, DC, 2017)
Reforming business licenses is part of a suite of products delivered by the World Bank group's investment climate advisory services, under the business operations practice. The approach to reforms highlighted in this handbook fits into the broader policy framework for business licensing reform and simplification. The framework paper provides the context for business licensing practices; establishes the key principles and concepts underpinning licensing; and gives an overview of licensing reform objectives, issues, and processes. It includes an overall introduction to the use (and abuse) of business licenses, and a further elaboration on the way business licensing reforms can be organized. This handbook is part of a suite of knowledge management products dedicated to business licensing. This handbook is written for business regulation practitioners. It aims to provide reformers with detailed information and guidance on how to implement fast-track, top-down licensing and regulatory reform projects. Its structure follows the process underpinning such reforms, taking readers step-by-step through the successive stages of reforms.